Disability as a Path to Spiritual Enlightenment: An Ethnographic Account of the Significance of Religion in Paralympic Sport - Howe, P. David (Journal of disability & religion, 2014)
This article explores the importance of spirituality amidst the culture that surrounds high performance athletes who have acquired impairments. In so doing, it highlights the way in which spirituality and religion may be used as a vehicle for dealing with issues of re-embodiment and how this might impact long-term athlete well-being. Featuring ethnographic data collected over the course of a number of Paralympic Games, the essay explores the act of re-embodiment and how being “re-born” in line with various religious frameworks is something to which elite athletes with a disability may turn in order to make sense of their place in the world. Drawing on literature from the field of religious studies as well as a critical theorization of disability, the essay sheds light on the relationship between sport and religion using the “imperfect” bodies of Paralympians as a catalyst to explore the importance and meaning of spirituality in the everyday existence of sportspeople with disabilities.